Nutrition Awareness and Oral Health among Dental Patients in Palestine: A Cross-Sectional Study - Manal M. H. Badrasawi; Nour H. Hijjeh; Rana S. Amer; Reema M. Allan; Mohammad Altamimi (Hindawi Limited, 2020)
Nutrition plays a key role in oral and dental health. Similarly, oral health affects nutrition status and diet intake. Consumption of much cariogenic nutrients such as sugar affects dental and gum health. The awareness of dietary practices that affect the oral health is an essential component in the dental care system. The knowledge of the dietary factors that affect the oral health is a major component in the treatment plan. In this vein, this study was conducted to determine the level of awareness of nutrition information affecting oral health among dental patients who visit the private and university dental clinics in West Bank, Palestine. A total of 169 patients were invited to join the study and signed the consent form. A pretested questionnaire was used to collect the required data which included patients' sociodemographics, medical history, oral care practices, dietary practices, and oral health-related nutritional awareness. Face and content validity were verified, followed by a pilot study to determine the questionnaire reliability alpha, and the data were collected from October to November 2018. The Construct Validation was done using the Rasch measurement model, and the descriptive statistical analysis was done to determine the level of awareness and the difference among the groups using SPSS version 21. The total mean score of the nutrition awareness was (9.3 ± 2.8), with higher level of nutrition awareness among females, and the highest score was 16 out of 17. The good oral health condition was reported among 44%, fair 32%, poor 16%, and bad 10% while excellent oral health was reported among only 5% of the participants. There was no significant relationship between level of nutritional awareness with economic status, level of education, or area of living. For oral health, females showed significantly better oral and gum health levels (p<0.05). The overall level of nutrition knowledge among the participants is insufficient. These results point to the need for oral health and nutrition educational courses and programs to improve oral and nutritional awareness and knowledge among Palestinian people and dental patients in particular. Improving the dietary habits and oral practices with lifestyle changes should also be encouraged.